The K Team [compact disc, unabridged] - Rosenfelt, David (Rosenfelt, David. K Team novels., 2020)
Corey Douglas and his K-9 partner, Simon Garfunkel, have recently retired from the police force. Not ready to give up the life yet, they come up with a proposal for fellow former cop, Laurie Carpenter, and her investigating partner, Marcus. Laurie and Marcus, who help out Laurie's lawyer husband Andy on cases, have been chafing to jump back into investigating on their own, so they are in. They call themselves the K Team, in honor of Simon. Their first job as private investigators comes to them from Judge Henry Henderson, who's known as a very tough but fair judge, and they've all come up against him in court at one time or another. Though it's hard to believe, Judge Henderson is being blackmailed and extorted, and he doesn't want to involve the police. He needs the K Team to figure out why.